2021
DOI: 10.3389/fphar.2021.648244
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Alirocumab for the Secondary Prevention of Cardiovascular Events after Myocardial Infarction in the Chinese Setting

Abstract: Background: Proprotein convertase subtilisin/kexin type 9 inhibitor alirocumab reduce ischemic events; however, the cost-effectiveness remains uncertain. This study sought to evaluate its economic value in patients with myocardial infarction (MI) from the Chinese healthcare perspective.Methods: A state-transition Markov model was developed to determine the cost-effectiveness of alirocumab for preventing recurrent MI, ischemic stroke and death. Preventative effect of the therapy was gathered from ODYSSEY OUTCOM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The American College of Cardiology/American Heart Association and European Society of Cardiology guidelines recommend prior administration of ezetimibe for cost-effectiveness [17,26]. This is also relevant because of the cost considerations that are associated with the introduction of the PCSK9 antibody [16,27,28]. Temporary administration of PCSK9 agents has been noted to cause regression of plaques in the coronary arteries [29] and, similar to statins, this may lead to legacy effects of the PCSK9 antibody.…”
Section: Discussionmentioning
confidence: 99%
“…The American College of Cardiology/American Heart Association and European Society of Cardiology guidelines recommend prior administration of ezetimibe for cost-effectiveness [17,26]. This is also relevant because of the cost considerations that are associated with the introduction of the PCSK9 antibody [16,27,28]. Temporary administration of PCSK9 agents has been noted to cause regression of plaques in the coronary arteries [29] and, similar to statins, this may lead to legacy effects of the PCSK9 antibody.…”
Section: Discussionmentioning
confidence: 99%
“…This model has been used in recent studies [33][34][35][36]. The model cycle length was 1 year, and half-corrections were applied.…”
Section: Model Structurementioning
confidence: 99%
“…Both early revascularization and late chronic disease management impose a tremendous economic burden on limited healthcare resources [2]. Several studies have reported the findings of pharmaco-economic assessments of aspirin, statins, etc., used for primary or secondary prevention in patients with cardiovascular disease [33][34][35][36]. As an efficient add-on therapy, there have been no studies on the cost-effectiveness of SBP for CAD in Chinese populations.…”
Section: Introductionmentioning
confidence: 99%
“…In March of 2018, the cost of alirocumab was substantially reduced to an average cost of up to 5850 USD per year, and soon after the cost of evolocumab was similarly reduced. Even at the discounted price, subsequent cost-effective analyses found the PCSK9 inhibitors in general not to be cost-effective [8][9][10]. The aim of this study was to evaluate prescribing patterns of PCSK9 inhibitors, and the characteristics of patients prescribed one before and after the price reduction for real-world patients.…”
Section: Introductionmentioning
confidence: 99%